D. Pedro II e a emancipação dos escravos - Alcântara, Mauro Henrique Miranda de (2013)
When you mention the topic abolition of slavery in Brazil, automatically refers to the figure of the Princess Isabel. Probably for having been responsible for the signing of the "Áurea" Law, which extinguished slavery in the country. This relation continued until today. However, it was during the reign of D. Pedro II that we saw the unfolding of the abolitionist process: since the end of the slave trade in 1850 to the signing of that law in 1888. Through biographies about the monarch and discourse analysis of the “Fala do Trono”, we seek to verify their importance in the process that ended the slavery regime and brazilian the projection discourse on this theme. To analyze the dimension of historical process of extinction of slavery in the country, there were readings / analyzes historical works on the topic. Realizing the problematics involving biographical writing, use the reading of Pierre Bourdieu, we pay attention to them. On the other hand, to verify the importance and possibilities of reading this genre, we admitted him in the writings of François Dosse, Giovanni Levi and Philippe Levillain. Regarding the analysis of the discourse of “Fala do Trono”, we seek contributions Michel Pêcheux, Paul Henry, Dominique Maingueneau, Antoine Prost and John R. Searle. We conduct readings / analysis of biographies about the Emperor to visualize how they portrays their relationship about the power and its role in the process that brought an end the enslavement. We found more than forty biographical works on the monarch. However, due to the impossibility of exhausting the analysis of such readings, we decided to pick only the latest and greatest documentary basis. View of this, we performed the reading and analysis of biographies of Roderick J. Barman (Citizen Emperor), Lilia Moritz Schwarcz (The Barbs Emperor), José Murilo de Carvalho (Pedro II), Napoleão Paulo Nogueira da Silva (Pedro II and his destiny) and Lídia Besouchet (Pedro II and the nineteenth century). To better perform the task of analyzing “Falas do Trono”, we divide the analysis into three periods: the period of the adoption of the law has put in the illegal slave trade (1841-1857). Discourses surrounding the approval of the first abolitionist legislation: the Law of the Free Womb (1867-1872). Finally, the speeches of the final period of the abolition of slavery (1883-1889). Visualize the relationship between the Emperor D. Pedro II and the process of abolition of slavery in Brazil, is therefore the object of this work.